O desafio da reintegraç\~ao social do preso: Uma pesquisa em estabelecimentos prisionais - Carla Coelho de Andrade; Almir de Oliveira Júnior; Alessandra de Almeida Braga; André Codo Jakob; Tatiana Daré Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This article is based on a survey conducted within the framework of a technical cooperation agreement between the National Justice Council (CNJ) and the Institute for Applied Economic Research (IPEA), with the purpose of presenting an overview of criminal recidivism based on data collected in some States of the country (Alagoas, Minas Gerais, Pernambuco, Paraná, and Rio de Janeiro). It presents the results of a qualitative character investigation focused on the theme of social reintegration, understood as the actual action of the government before the challenge of criminal recidivism. Thus, it outlines the existing initiatives, the implementation strategies, the development of actions and the perceptions about social reintegration from the perspective of different actors, considering their respective insertions in the institutional world: judges; penal execution operators and agents involved in the implementation of the programs (technical team of professionals from government agencies, prison staff, teachers, social workers, psychologists); prisoners and internees.
Keywords: K42; 330; Criminal enforcement; Law enforcement; Prisons; Social reintegration